Implementasi Area Traffic Control System (ATCS) di Berbagai Wilayah di Indonesia Sebagai Penerapan Smart Mobility - Siti Kholishoh Ismatul Aini; Sekar Alka Bawono Putri; Ivan Darmawan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Smart Mobility is a crucial concept in the development of smart cities, focusing on integrating technology to create an efficient, safe, comfortable, and environmentally friendly transportation system. The implementation of the Area Traffic Control System (ATCS) as part of Smart Mobility aims to optimize traffic management in urban areas. This study examines the implementation of ATCS in various cities across Indonesia, highlighting the challenges faced in its operation, such as limited financial resources, equipment malfunctions, and low public awareness of traffic compliance. This literature review uses a bibliographic approach to gather data from various research journals related to ATCS implementation in major cities such as Medan, Batam, Bandung, Balikpapan, and Ambon. The findings show that while ATCS has provided benefits in terms of improving traffic flow in certain locations, there are still several barriers in the maintenance and development of this system. Therefore, this study suggests improving human resources quality, increasing funding and facilities, as well as more stringent evaluation and supervision to ensure ATCS functions optimally in supporting Smart Mobility in Indonesia.